EFFECTUALNESS OF INSTAGRAM REELS IN ENHANCING STUDENTS’ LEXICAL KNOWLEDGE - Fadhlillah, Aniesah; Ro'ifah, Ro'ifah; Yunianti, Sofi (Universitas PGRI Sumatera Barat, 2024)
Educational environment requires teachers to embrace innovation and creativity to facilitate learning through the use of technology. This research use Instagram Reels because it is the newest social media that is very easy to use and always used by students. The aim of this research is to examine the effectualness of Instagram Reels on enhancing students' lexical in learning English at one of the high schools in Sidoarjo. This research used a quantitative approach with pre-experimental design. Data was collected from class XII MAS Tanada Waru, Sidoarjo, totalling 26 students as samples. The instrument used was pre-test and post-test which were carried out after and before treatment, SPSS, and learning observation. This research found that the mean score of students lexical achievement taught by using Instagram Reels is 88.46 in the post-test, 26.54 higher than the pre-test (61.92). It showed that students have succeeded in mastering the learning material due to the use of Instagram Reels. This research provides useful implications, namely with innovation and creativity possessed by educators in creating interactive and educative learning media can enhanced the achievement of students lexical knowledge.